"Adjusting internal organs and dredging channel" electroacupuncture treatment prevents the development of diabetic peripheral neuropathy by downregulating glucose‐related protein 78 (GRP78) and caspase‐12 in streptozotocin‐diabetic rats. Issue 12 (6th May 2019) - Pan, Hong; Huang, Haipeng; Zhang, Liying; Ma, Shiqi; Yang, Hongmei; Wang, Hongfeng
Abstract: Background: The clinical efficacy of electroacupuncture in treating diabetic peripheral neuropathy (DPN) is significant, but the underlying mechanism of action is not clear. Considering that glucose‐regulated protein 78 (GRP78) and caspase‐12 are major proteins participating in cell apoptosis, we investigated the effects of "adjusting internal organs and dredging channel" electroacupuncture therapy on GRP78 and caspase‐12 levels in streptozotocin (STZ)‐diabetic rats to elucidate the mechanism of action. Methods: Rats were first divided into two groups: one group was rendered diabetic with a single injection of 50 mg/kg STZ, whereas the other normal control group was injected with an equivalent volume of citrate buffer. The STZ‐diabetic rats were randomly divided into three groups: model control and electroacupuncture‐ and mecobalamin‐treated groups. After 12 weeks treatment, the therapeutic efficacy of electroacupuncture was assessed using sciatic nerves isolated from rats. In the electroacupuncture group, rats were treated by electroacupuncture for 20 minutes once daily for 6 days each week, with 1 day off, for 12 consecutive weeks. The selected acupressure points include bilateral acupressure points of BL13 (Fehu), BL20 (Pishu), BL23 (Shenshu), LI4 (Hegu), LR3 (faichong), ST36 (Zusanli), and SP6 (Sanyiniiao). Acupressure points were stimulated using a HuaTuo SDZ‐V Electric Acupuncture Therapy Apparatus. The acupressure points of BL13 and BL23, as well as SP6 and LR3, were connected on the same side with a dilatational wave of 3 Hz (frequency ratio of 1 : 5) to stimulate the parts of the body to the extent that could be tolerated by the rat. As for the mecobalamin‐treated groups, mecobalamin was administrated to rats intragastrically at a dose of 20 mg/kg once daily for 12 consecutive weeks. Immunofluorescence and western blot analysis were used to determine GRP78 and caspase‐12 levels in sciatic nerves. In addition, cell apoptosis in sciatic nerves was determined using the terminal deoxyribonucleotidyl transferase‐mediated dUTP‐digoxigenin nick end‐labeling (TUNEL) assay. Results: Electroacupuncture markedly reduced the pathological injury to sciatic nerves in STZ‐diabetic rats. Moreover, electroacupuncture significantly downregulated GRP78 and caspase‐12 and reduced cell apoptosis of sciatic nerves in DPN rats. Conclusions: Electroacupuncture improved DPN by downregulating GRP78 and caspase‐12 and reducing cell apoptosis of sciatic nerves in STZ‐diabetic rats, and further inhibited the occurrence of endoplasmic reticulum stress, thus preventing sciatic nerve injuries. Abstract : Highlights Electroacupuncture treatment of diabetic peripheral neuropathy (DPN) reduced cell apoptosis of sciatic nerves in diabetic rats, inhibited the occurrence of endoplasmic reticulum stress, and thus prevented sciatic nerve injuries. The treatment effectiveness of electroacupuncture for DPN may be mediated via downregulation of glucose‐related protein 78 (GRP78) and caspase‐12. 摘要: 背景: 电针治疗糖尿病周围神经病变(diabetic peripheral neuropathy，DPN)临床疗效显著，但其作用机制尚不清楚。葡萄糖调节蛋白78 (GRP78)和caspase‐12是参与细胞凋亡的主要蛋白。因此，为了阐明其作用机制，我们研究了"调脏通络"电针治疗对链脲佐菌素(STZ)诱导的糖尿病大鼠中GRP78和caspase‐12水平的影响。 方法: 首先将大鼠分为两组:一组为糖尿病组，采用一次性腹腔注射STZ，剂量为50 mg/kg，制备糖尿病模型；另一组为正常对照组，注射等量柠檬酸缓冲液。将STZ诱导的糖尿病大鼠随机分为3组:模型对照组、电针治疗组和甲钴胺治疗组。治疗12周后，取大鼠坐骨神经观察电针的疗效。其中电针组每次治疗20 min，每日1次，每周6天，休息1天，连续12周，选择的穴位包括双侧BL13(肺俞)、BL20(脾俞)、BL23(肾俞)、LI4(合谷)、LR3(太冲)、ST36(足三里)、SP6(三阴交)。采用华陀SDZ‐V电针治疗仪，以同侧BL13、BL23和同侧SP6、LR3为电针连接对穴，取疏密波，频率为3Hz(频率比为1:5)刺激穴位，以大鼠能够耐受为度。甲钴胺治疗组大鼠进行甲钴胺20 mg/kg灌胃治疗，每日1次，连续12周。免疫荧光法和western blot法检测坐骨神经GRP78和caspase‐12水平，采用TUNEL试剂盒检测坐骨神经细胞凋亡。 结果: 电针明显减轻了STZ诱导的糖尿病大鼠坐骨神经的病理损伤。此外，电针还能显著下调DPN大鼠的GRP78和caspase‐12水平，减少坐骨神经细胞凋亡。 结论: 电针疗法通过下调GRP78和caspase‐12水平，减少糖尿病大鼠坐骨神经细胞凋亡，改善DPN，进一步抑制内质网应激的发生，从而预防坐骨神经损伤。